Hippocampal vulnerability to hyperhomocysteinemia worsens pathological outcomes of mild traumatic brain injury in rats - Flaubert Tchantchou; Ru-ching Hsia; Adam Puche; Gary Fiskum (Journal of Central Nervous System Disease, 2023)
Background Mild traumatic brain injury (mTBI) generally resolves within weeks. However, 15-30% of patients present persistent pathological and neurobehavioral sequelae that negatively affect their quality of life. Hyperhomocysteinemia (HHCY) is a neurotoxic condition derived from homocysteine accumulation above 15 μM. HHCY can occur in diverse stressful situations, including those sustained by U.S. active-duty service members on the battlefield or during routine combat practice. Mild-TBI accounts for more than 80% of all TBI cases, and HHCY exists in 5-7% of the general population. We recently reported that moderate HHCY exacerbates mTBI-induced cortical injury pathophysiology, including increased oxidative stress. Several studies have demonstrated hippocampus vulnerability to oxidative stress and its downstream effects on inflammation and cell death. Objective This study aimed to assess the deleterious impact of HHCY on mTBI-associated hippocampal pathological changes. We tested the hypothesis that moderate HHCY aggravates mTBI-induced hippocampal pathological changes. Methods HHCY was induced in adult male Sprague-Dawley rats with a high methionine dose. Rats were then subjected to mTBI by controlled cortical impact under sustained HHCY. Blood plasma was assessed for homocysteine levels and brain tissue for markers of oxidative stress, blood-brain barrier integrity, and cell death. Endothelial cell ultrastructure was assessed by Electron Microscopy and working memory performance using the Y maze test. Results HHCY increased the hippocampal expression of nitrotyrosine in astroglial cells and decreased tight junction protein occludin levels associated with the enlargement of the endothelial cell nucleus. Furthermore, HHCY altered the expression of apoptosis-regulating proteins α-ii spectrin hydrolysis, ERK1/2, and AKT phosphorylation, mirrored by exacerbated mTBI-related hippocampal neuronal loss and working memory deficits. Conclusion Our findings indicate that HHCY is an epigenetic factor that modulates mTBI pathological progression in the hippocampus and represents a putative therapeutic target for mitigating such physiological stressors that increase severity.